2008
DOI: 10.1063/1.2980037
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile memory effect based on gold nanoparticles doped ferroelectric liquid crystal

Abstract: Nonvolatile memory effect based on gold nanoparticles ͑GNPs͒ doped deformed helix ferroelectric liquid crystal ͑DHFLC͒ has been observed. This observed memory effect has been attributed to electric field induced charge transfer from liquid crystal molecules to the GNPs and the stabilization of helix deformation of DHFLC material, which occurs on the application of electric field beyond a critical field. The memory effect has been analyzed by polarizing optical microscopy, high-resolution transmission electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
47
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 100 publications
(47 citation statements)
references
References 32 publications
0
47
0
Order By: Relevance
“…[1][2][3] Nanoparticle doping technology provides a more convenient and flexible approach for the modification of liquid crystal (LC) materials and for designing new and improved devices based upon LCs. The minute addition of nanoparticles (NPs) to LC materials has improved many special characteristics in the form of frequency modulation response, 4 non-volatile memory effect, 5 fast electro-optic response, 6 low driving voltage, 7 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Nanoparticle doping technology provides a more convenient and flexible approach for the modification of liquid crystal (LC) materials and for designing new and improved devices based upon LCs. The minute addition of nanoparticles (NPs) to LC materials has improved many special characteristics in the form of frequency modulation response, 4 non-volatile memory effect, 5 fast electro-optic response, 6 low driving voltage, 7 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The addition of gold NPs in ferroelectric liquid crystals ͑FLCs͒ has been reported earlier in order to observe low threshold and nonvolatile memory effect. 8,9 Zhang et al 10 observed the lowering of threshold voltage of CdS NPs doped 4-pentyl-4'-cyanobiphenyl ͑5CB͒ twisted nematic cells by 25%. The low power operation of vertically aligned LC by doping a minute amount of anatase TiO 2 -NPs have been observed by Lee et al 11 Zinc oxide ͑ZnO͒ has been employed in a variety of devices such as gas sensors, solar cells, luminescent materials, and transparent conducting coatings due to its wide range of optical and electrical properties.…”
mentioning
confidence: 99%
“…24,25 Our group has demonstrated the nonvolatile memory effect based on GNPs doped DHFLC material ͑FLC 6304͒. 26 In the present studies, we characterized newly synthesized DHFLC material, namely LAHS19, using different experimental techniques and discussed the enhancement of luminescence intensity in GNPs doped DHFLC material on the basis of interaction of DHFLC molecules with GNPs. It has also been found that the luminescence intensity of GNPs doped DHFLC material can be tuned by varying the concentrations of GNPs.…”
mentioning
confidence: 92%